Smelly locker : silly dilly school songs - Katz, Alan.; Catrow, David (New York : Margaret K. McElderry Books, 2008)
Well-known songs, including "Oh Susannah" and "Take Me Out to the Ballgame," are presented with new words and titles, such as "Heavy Backpack!" and "I Don't Want to Do Homework!"
2.5
K-3
Keywords: Children's songs, English -- United States -- Texts; Schools -- Songs and music -- Texts; Humorous songs -- United States -- Texts; Schools -- Songs and music; Humorous songs; Songs; Schools -- Songs; Humorous songs; Songs